(untitled) (Fiep Bulletin - online, 2015)
This article, based on a bibliographical study, consists of theoretical analysis and experience reports related to the applicability of socio-educational psychodramatic practice in dance and theater workshops at Colégio Militar de Salvador (CMS). The extracurricular activities happened from 2009 to 2014 during the afternoon shift. They were essential for the development of spontaneity, creativity, sensibility, besides using the ludic, inter, and transdisciplinary practices to enable the performing arts in the citizenship, dialogical and ecology practices. These aspects, all together, increase the student perception on his/her own bodies as well as the need to enhance their cultural traits and to develop their psychosocial roles. The Edgar Morin framework was chosen because of the transdisciplinarity concepts, associated with motor practice in order to reinforce the holistic rhetoric in the contemporary human body reading. The dance at CMS has diachronic and dialogical dimensions, and draws attention to the pedagogical psychodrama, which involves the image constructions that favor the external feelings and truths that happen in everyday social lives. Once the physical conditioning does not enable the body expression, it is necessary to create some physical activity room to release the body to experience some situations so that the bonds can be both strengthened and facilitated. Thus, the Edgar Morin practices are considered the right agents that contribute to develop the emotional competences presented in the contemporary education. Therefore, dance is understood as a fundamental part in the process of knowledge construction, both enabling the literacy, the eco-pedagogy and exchanging unequal contents on creativity constructions.